Phosphatidylglycerol to Treat Chronic Skin Wounds in Diabetes - Yonghong Luo; Edymarie Vivaldi Marrero; Vivek Choudhary; Wendy B. Bollag (MDPI AG, 2023)
This review proposes the use of dioleoylphosphatidylglycerol (DOPG) to enhance diabetic wound healing. Initially, the characteristics of diabetic wounds are examined, focusing on the epidermis. Hyperglycemia accompanying diabetes results in enhanced inflammation and oxidative stress in part through the generation of advanced glycation end-products (AGEs), in which glucose is conjugated to macromolecules. These AGEs activate inflammatory pathways; oxidative stress results from increased reactive oxygen species generation by mitochondria rendered dysfunctional by hyperglycemia. These factors work together to reduce the ability of keratinocytes to restore epidermal integrity, contributing to chronic diabetic wounds. DOPG has a pro-proliferative action on keratinocytes (through an unclear mechanism) and exerts an anti-inflammatory effect on keratinocytes and the innate immune system by inhibiting the activation of Toll-like receptors. DOPG has also been found to enhance macrophage mitochondrial function. Since these DOPG effects would be expected to counteract the increased oxidative stress (attributable in part to mitochondrial dysfunction), decreased keratinocyte proliferation, and enhanced inflammation that characterize chronic diabetic wounds, DOPG may be useful in stimulating wound healing. To date, efficacious therapies to promote the healing of chronic diabetic wounds are largely lacking; thus, DOPG may be added to the armamentarium of drugs to enhance diabetic wound healing.